Biological and Morphological Changes of the Brain in Alzheimer’s Disease I - Urmanbekova Dilfuza Sanatullayevna; Boboxonova Robiyaxon Alisher qizi; Ergasheva Zebiniso Fazliddin qizi (American Journal of Bioscience and Clinical Integrity, 2025)
We review the key neurobiological processes observed in the development of Alzheimer’s disease, including beta-amyloid deposition, pathological transformation of tau protein, disruption of synaptic connections, inflammatory responses, and structural atrophy. We consistently describe the biophysiological changes that occur in the early and late stages of the disease.